Delineating the Detail: The Communication of Architectural Particulars, 1750-1872 - Bellin, Eric (ARCC Conference Repository, 2013)
In contemporary architectural practice, the notion of the architectural detail is complex and contentious. For many, ‘details’ are synonymous with the smallest scale of construction’s resolution. Others believe them to be a building’s ‘minimal units of signification’ and essential to the production of architectural meaning. And still others see the term as interchangeable with ornamentation. While there have been recent and notable contributions to the architectural detail’s theorization, the longer history of its etymological evolution and changing meanings in practice has yet to be written. As a means of clarifying our contemporary understanding of the meaning of the practice of detailing, this study intends an overview of one piece of this proposed history, exploring the dynamic relation between architectural details and their delineation in 18th and 19th century France and the United Kingdom. The word "detail” stems from the French de tailler, meaning "to cut up into pieces”, which would evolve into the cognate détail by the 18th century. The term referred to the ‘cutting’ of architecture into a collection of significant fragments, a process accomplished primarily via drawing as a means of both development and communication. This practice, however, would be brought to bear on an increasingly complex collection of things as designers responded to the emergence of new social, disciplinary, and technological conditions by the mid-19th Century. From issues of fire-protection to prefabrication and the growing rift between architects and engineers, the stage would be set for the haze of our contemporary understanding of detail. By analyzing a collection of delineated details from a series of critical moments from the late 18th to mid 19th centuries, this paper seeks to give a conceptual account of the practice of detailing as derived from an understanding of its shifting meanings in the history architectural discourse and practice.